2011
DOI: 10.1039/c0cc05326k
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman scattering with silver nanostructures generated in situ in a sporopollenin biopolymer matrix

Abstract: Silver nanoparticles were generated based on citrate reduction in the ultrastructure of the sporopollenin biopolymer of Ambrosia artemisiifolia (ragweed) and Secale cereale (rye). The nanoparticles enable the acquisition of SERS spectra and thereby a vibrational characterization of the local molecular structure of sporopollenin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…With regard to the high fluorescence background that has been observed in the Raman spectra of some pollen species , obtaining surface‐enhanced Raman scattering (SERS) rather than normal Raman spectra can provide significant improvements in the vibrational characterization of pollen, since the noble metal nanostructures that are used as SERS substrates provide efficient quenching of fluorescence together with high signal enhancement . Nevertheless, SERS spectral information from the outer coat highly depends on the portion of the sporopollenin ultrastructure that interacts with the metal nanoparticles and requires their integration in the structure, for example by in situ synthesis . So far, in automated species identification, Raman‐based classification relies mainly on pollen outer shell biochemistry .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the high fluorescence background that has been observed in the Raman spectra of some pollen species , obtaining surface‐enhanced Raman scattering (SERS) rather than normal Raman spectra can provide significant improvements in the vibrational characterization of pollen, since the noble metal nanostructures that are used as SERS substrates provide efficient quenching of fluorescence together with high signal enhancement . Nevertheless, SERS spectral information from the outer coat highly depends on the portion of the sporopollenin ultrastructure that interacts with the metal nanoparticles and requires their integration in the structure, for example by in situ synthesis . So far, in automated species identification, Raman‐based classification relies mainly on pollen outer shell biochemistry .…”
Section: Introductionmentioning
confidence: 99%
“…Optical and spectroscopic methods, also in combination with morphological information, have been shown to be applicable for pollen characterization and classification. Sensitive Raman spectroscopic tools, specifically Raman mapping and resonant Raman scattering, were used to characterize small physiological changes and selected biomolecular species in pollen grains …”
mentioning
confidence: 99%
“…Sensitive Raman spectroscopic tools, specifically Raman mapping and resonant Raman scattering, were used to characterize small physiological changes [26] and selected biomolecular species in pollen grains. [27][28][29] We have found that the MALDI-TOFMS spectra of pollen provide mainly information about sugars, proteins and glycoproteins in the pollen grain interior of some selected plant species. [17] Extending from this previous characterization work, here, we investigate the MALDI-MS data of 74 species from six families in two plant orders.…”
mentioning
confidence: 99%
“…Moreover, molecular changes during pollen germination could be monitored . We also reported the application of silver nanoparticles for surface‐enhanced Raman spectroscopy (SERS) for the characterization of the local molecular structure of sporopollenin, which represents a major part of the pollen shell …”
mentioning
confidence: 99%